Celiac axis stenosis is an underestimated risk factor for increased morbidity after pancreatoduodenectomy - Saeedi, Mohammed al; Sauer, Hendrik Benedikt; Ramouz, Ali; Deisenhofer, Julian; Frank-Moldzio, Leonie; Bruckner, Thomas; Loos, Martin; Mayer, Philipp; Klauß, Miriam; Kulu, Yakup; Berchtold, Christoph; Hoffmann, Katrin; et al. (Annals of surgery, 2023)
Objective: - To assesses the prevalence and severity of CAS in patients undergoing PD/total pancreatectomy and its association with major postoperative complications after PD. - Summary of background data: - CAS may increase the risk of ischemic complications after PD. However, the prevalence of CAS and its relevance to major morbidity remain unknown. - Methods: - All patients with a preoperative computed tomography with arterial phase undergoing partial PD or TP between 2014 and 2017 were identified from a prospective database. CAS was assessed based on computed tomography and graded according to its severity: no stenosis (<30%), grade A (30%-<50%), grade B (50%-≤80%), and grade C (>80%). Postoperative complications were assessed and uni- and multivariable risk analyses were performed. - Results: - Of 989 patients, 273 (27.5%) had CAS: 177 (17.9%) with grade A, 83 (8.4%) with grade B, and 13 (1.3%) with grade C. Postoperative morbidity and 90-day mortality occurred in 278 (28.1%) patients and 41 (4.1%) patients, respectively. CAS was associated with clinically relevant pancreatic fistula (P=0.019), liver perfusion failure (P=0.003), gastric ischemia (P=0.001), clinically relevant biliary leakage (P=0.006), and intensive care unit (P=0.016) and hospital stay (P=0.001). Multivariable analyses confirmed grade B and C CAS as independent risk factors for liver perfusion failure; in addition, grade C CAS was an independent risk factor for clinically relevant pancreatic fistula and gastric complications. - Conclusions: - CAS is common in patients undergoing PD. Higher grade of CAS is associated with an increased risk for clinically relevant complications, including liver perfusion failure and postoperative pancreatic fistula. Precise radiological assessment may help to identify CAS. Future studies should investigate measures to mitigate CAS-associated risks.